STRUCTURAL AND FUNCTIONAL ORGANIZATION OF PERSONALITY SPACE OF STUDENTS YOUTH - Virna, Zhanna; Koshyrets, Viktor (Psychological Prospects Journal, 2014)
Virna Zh. P., Koshyrets V. V. Structural and Functional Organization of Personality Space of Students Youth. The article concretizes the conceptual and methodological aspects of the personality phenomenon study concerning space of students youth in the author’s position within its structural and functional organization. Central principles of the research position of personality space study in the form of an internal integrated image of subjective characteristics were outlined providing an adequate level of social and psychological adaptation and formation of social maturity, self-assertiveness and self-actualization of modern students. The main structural components of personality space and their specific functions are denoted: adaptation component has got adaptive, controlling and protective functions; motivation component implements stabilizing, identifying and innovative functions; personality and behavior components contain organizing, communicative and accumulating functions. The functional features of the personality space structural components and its psychological boundaries are analysed; quality characteristics as integrity, self-organization and openness of personality space are distinguished. The program of empirical research as well as the complex of mathematical processing methods confirm the concept of understanding the personality space as the form of internal coherence of a student with life circumstances, accompanied by the configuration of adaptation, motivation, personality and behaviour components peculiarities. High indexes of psychological space sovereignty of students in most cases are caused by such characterological qualities and ways of interaction with others as responsibility, straightforwardness, mistrust and disposition to personal autonomy. Semantic representation of «life image» of the students by the method of finding semantic universals of stable and similar evaluations totality allows to allocate such features as compromise, positive, egoistic, open, democratic ones. Keywords: personality space, psychological space sovereignty, life image, social and psychological adaptation, social maturity, self-assertiveness, self-actualization, students youth.